If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x+x+3=-5(x+x+1)-114
We move all terms to the left:
x+x+3-(-5(x+x+1)-114)=0
We add all the numbers together, and all the variables
x+x-(-5(2x+1)-114)+3=0
We add all the numbers together, and all the variables
2x-(-5(2x+1)-114)+3=0
We calculate terms in parentheses: -(-5(2x+1)-114), so:We get rid of parentheses
-5(2x+1)-114
We multiply parentheses
-10x-5-114
We add all the numbers together, and all the variables
-10x-119
Back to the equation:
-(-10x-119)
2x+10x+119+3=0
We add all the numbers together, and all the variables
12x+122=0
We move all terms containing x to the left, all other terms to the right
12x=-122
x=-122/12
x=-10+1/6
| 2/3a-6=1/3a-9 | | 15.7·3.09+15.7·2.91=xx= | | 5x+62=3x+84 | | .25+6x(4-2x)=-95.75 | | 5x=24.50 | | -4(2x+4)=-16x+5 | | 500-2x=220 | | 5+17x=1495 | | y/2=(2y-18) | | 15=5x~13 | | 3/x=20/100 | | (8x^2-12)=(7x^2-4x) | | .25+16x(6-2x)=-127.75 | | 38=5+6a | | 8x+-16=-16x+5 | | 8x-7+2x=13 | | 146=9x+11 | | x/8-2=3/16 | | 6~8x=36 | | X=6+2/3y | | 2-9m+5+4m=2+8(5) | | 4.5+8x(7-2x)=-27.5 | | y/4+5=-4 | | -8x+11+9x=7+x+14 | | 3s-6-s=s=9 | | 3.95+0.08x=8.95+0.06x | | 3.95+0.08x=8.95+0.06 | | 2(x-2)=x+9 | | 24x-18=18 | | 7+1/9=2+4/5=m | | 3x-4+2x-2=14 | | 12x-5=4+1 |